NEUROMARKETING AND CONSUMER DECISION-MAKING OF CINEMA OUTLETS: UNDERSTANDING THE PSYCHOLOGICAL DRIVERS OF SALES (American Journal of Interdisciplinary Research and Development, 2025)
This study aims to investigate the relationship between neuromarketing and consumer decision-making: understanding the psychological drivers of sales. The research design adopted for this study is quantitative, utilizing a cross-sectional survey method to collect data from customers of cinema outlets in Port Harcourt. They were ten (10) cinema outlets in Port Harcourt. The study is a census and all the firms were studied. Five (5) copies of questionnaire were administered to each of the ten (10) to give us a total of fifty (50) respondents and filled by the consumers. The Spearman Rank Correlation tool was adopted with the aid of Statistical Package for Social Sciences (SPSS version 23.0). The findings of this study indicate that attention has a significant positive relationship with consumer decision-making, as evidenced by the significant positive correlation coefficients with visit intention. The results also show that the memory processing has a significant positive relationship with visit intention. Finally, emotional processing has a significant positive relationship with visit intention. The study concluded that neuromarketing has a significant contribution on consumer decision-making of cinema outlets in Port Harcourt. The study therefore recommended amongst others that, cinema outlets should focus more on these stimuli and use it to grab attention and help retain the ads in consumers memories.